ANALISIS INOVASI TEKNOLOGI DALAM MANAJEMEN KINERJA PERUSAHAAN ASURANSI - Zainarti Zainarti; Putri Wulandini Sagala (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The main idea of this article is an overview and analysis of technological innovation in the insurance industry and insurance company performance management. First of all, the author has characterized the factors driving innovative development in the insurance industry. Second, innovation in the financial sector is described as discovery and adoption. The main part of the journal could be based on an overview of the use of technological innovations (such as software, analytics, sensors, algorithms) for effective insurance value chains. In the final part, the author makes a SWOT analysis of technological innovation